STRUCTURE AND GROWTH OF STEARATE MONOLAYERS ON CALCITE: FIRST RESULTS OF AN IN SITU X-RAY REFLECTIVITY STUDY1 - Fenter P.; Sturchio N.C. (My University, 1999)
The adsorption of organic molecules at mineral-fluid interfaces has a profound influence upon geochemical reaction and transport processes, yet little is known about the in situ structures or properties of organic layers at mineral-fluid interfaces. We describe an X-ray reflectivity study of stearate monolayers adsorbed at the calcite surface from methanolic solutions. Using these measurements we are able to determine important aspects of the in situ structure, bonding, adsorption, and growth mechanisms of stearate monolayers. The experimental approach demonstrated here can be applied widely in studying the interaction of organic molecules with mineral surfaces in aqueous systems.